Stingless Beehive Entrance Shape and Size in the Imbo Putui Customary Forest, Kampar Regency - Novia Rahman; Gesriantuti, Novia; Badrun, Yeeri; Syarif, Nuskan; Tas'ad, Said Faizan (Photon: Jurnal Sain dan Kesehatan, 2025)
Imbo Putui Customary Forest supports high biodiversity, including stingless bees; however, data regarding the specific morphology of their nest entrances in this region remain limited. This study aimed to characterize the entrance funnel length, diameter, nest height, color, shape, and nesting habitat conditions of stingless bees in Imbo Putui Forest. The study employed a survey method with purposive sampling across three zones: roadside (Zone I), forest interior (Zone II), and riparian/oil palm plantation areas (Zone III). Eight stingless bee species were identified: Heterotrigona itama, Tetragonula laeviceps (black and yellow), Tetragonilla collina, Tetragonula drescheri, Tetragonula testaceitarsis, Tetragonula iridipennis, and Homotrigona fimbriata. Nest measurements indicated funnel lengths of 1–27 cm, entrance diameters of 5–20 mm, and nest heights ranging from 1 cm to 1000 cm. Morphologically, the nest entrances were predominantly round or oval in shape, with colors consistently ranging from brownish black to grayish brown.